OPTIMIZATION OF TEMPERATURE CELLULOSE PRODUCING BACTERIAL ISOLATES FROM DRAGON FRUIT (Hylocereus polyrhizus) - Nurung, Ayyub Harly; Widowati, Fairuz Dyah; Herwin, Herwin; Fitriana, Fitriana (Journal Microbiology Science, 2021)
Isolation of bacterial cellulose from fruits in traditional market of Makassar have been done. This objective of this research was to determine optimum temperature of isolate bacteria that produce cellulose from Dragon fruit (Hylocereus polyrhizus) using dilution agar method. Isolation of bacteria produced cellulose using Hestrin-Schramm agar (HSA) obtain 5 (five) isolate NB02, NB03, NS01 and NS02. The result of screening activity showed that isolate NB04 has a potential as bacteria produce cellulose. The temperature optimize of NB04 has been done at 25oC and 40oC. Based on research results showed that optimum temperature for NB04 was at 25oC and has highest cellulose content at 1,29 g.